2021
DOI: 10.18632/aging.202383
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of lncRNAs N6-methyladenosine modification in colorectal cancer

Abstract: Background: Long non-coding RNAs (lncRNAs) and their N6-methyladenosine (M6A) modifications are involved in cancer occurrence and development. Methods: lncRNA M6A modification in colorectal cancer (CRC) was comprehensively analyzed for the first time. Results: M6A levels of lnRNAs in CRC tissues were higher than those in tumor-adjacent normal tissues. A total of 8,332 M6A peaks were detected in 6,690 lncRNAs in CRC tissues. Approximately 91% of the modified lncRNAs had unique M6A modifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Similarly, Yuan et al constructed a lncRNAs prognostic model in liver cancer, and twenty-seven immune-related lncRNAs were screened by univariate Cox regression, the results show that AL049840.4 has prognostic value in liver cancer [35]. In addition, Zuo et al found that the m6A level of lncRNAs in CRC tissue was significantly higher than that in NATs and the GO and KEGG results showed that the lncRNAs modified by m6A can affect the occurrence and development of CRC by biological processes, cell composition, and molecular function [36]. These results suggest that lncRNA plays a vital role in predicting tumor prognosis and clarifies the relationship between lncRNA and m6A, which is beneficial to discovering new targets and treating tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Yuan et al constructed a lncRNAs prognostic model in liver cancer, and twenty-seven immune-related lncRNAs were screened by univariate Cox regression, the results show that AL049840.4 has prognostic value in liver cancer [35]. In addition, Zuo et al found that the m6A level of lncRNAs in CRC tissue was significantly higher than that in NATs and the GO and KEGG results showed that the lncRNAs modified by m6A can affect the occurrence and development of CRC by biological processes, cell composition, and molecular function [36]. These results suggest that lncRNA plays a vital role in predicting tumor prognosis and clarifies the relationship between lncRNA and m6A, which is beneficial to discovering new targets and treating tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Methylation was positively correlated with lncRNA expression levels in CRC and normal tissues adjacent to tumors. 45 …”
Section: M6a Rna Modificationmentioning
confidence: 99%
“…About 91% of the modified lncRNAs had a unique m6A modification peak, and a total of 383 lncRNAs were differentially methylated in CRC. 101 Ni et al found that lncRNA GAS5 expression negatively correlates with YAP and YTHDF3 protein levels in tumors from patients with CRC, and YAP activation is an important participant in a variety of cancers including CRC. The researchers found that the lncRNA GAS5 modified by m6A is negatively regulated by m6A “readers” YTHDF3, and further inhibits the progress of CRC by interacting with YAP to trigger its phosphorylation and degradation process.…”
Section: M6a Rna Methylation Modification and Colorectal Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated that m6A-related lncRNAs can reliably predict the prognosis of low-grade glioma, lung adenocarcinoma, and gastric cancer ( Tu et al, 2020 ; Wang et al, 2021a ; Wang et al, 2021b ). Luo et al( Zuo et al, 2021 ) further observed that m6A-related lncRNAs were associated with the occurrence and development of CRC, indicating that they may be an accurate prognostic factor for early-stage CRC.…”
Section: Introductionmentioning
confidence: 99%